Composition and distribution of bacterial communities and potential radiation-resistant bacteria at different elevations in the eastern Pamirs - Zhu, Jing; Wang, Hui-Nan; Tang, Qi-Yong; Gu, Mei-Ying; Zhang, Zhi-Dong (Frontiers in Microbiology, 2024)
Altitude and ultraviolet (UV) radiation may affect the community composition and distribution of microorganisms in soil ecosystems. In this study, 10 49 soil samples from 10 locations were collected from different elevations on the eastern Pamir Plateau and analyzed for soil microbial community structure and function using high-throughput sequencing. The results showed that soil samples from different elevations of the eastern Pamir Plateau contained 6834 OTUs in 26 phyla and 399 genera. The dominant phyla common to different elevations were Actinobacteria, Proteobacteria, Bacteroidota, Acidobacteriota, and Gemmatimonadota. The dominant genera were Rubrobacter, Sphingomonas, Nocardioides, and Solirubrobacter. Species richness increased slightly with elevation, and there were significant differences in community composition between the elevations. Elevation and UV exposure are important factors that drive changes in bacterial communities. The results of the KEGG pathway showed that drug resistance, antineoplastic, aging, replication, and repair were enhanced and then slightly decreased with increasing elevation. Bacterial communities at different elevations were rich in radiation-resistant microorganisms, and the main genera were Rubrobacter, Sphingomonas, Nocardioides, Pontibacter, and Streptomyces. The findings have shown the composition and distribution of bacterial communities at different elevations on the Eastern Pamir Plateau. Potentially radiation tolerant microbial species were also examined. The results are of considerable importance for the succession of bacterial microorganisms in the plateau region, the study of radiation 带格式的: 段落间距段后: 0 磅 tolerant bacterial germplasm resources, and the application of biofunctionality.